The Development of Institutional Base for the Implementation of Adult Population Financial Literacy Programs in Russia - O. V. Kuznetsov; A. V. Ivanov; I. S. Shevalkin; N. V. Vorovsky (Управленческие науки)
The relevance of studying problems related to the development of an institutional framework for implementation of adult population financial literacy is caused by the following circumstances: the need for State-level policies related to raising financial literacy of various categories of the population; the definition of mechanisms to protect the rights of financial services consumers; formation of prudent financial behavior of Russia citizens; further functioning of the Regional Advisory and methodical maintenance of population advisory centers in the financial services market; the increase in the number of consultants providing financial advisory services to various categories of adult population on a pro bono basis. The multidimensional teaching analysis of consulting trainers in the Centre of Excellence is applied as a method performed by regional consulting methodical centers since April, 2016 till March, 2017. Based on such analysis, the conclusions are made; the priorities and proposals for the institutional framework development for the implementation of adult literacy financial programs are defined.